Improving Food Systems through Agriculture Transformation in Africa - Oluch, Mel (2021)
Mel Oluch SPECIAL EVENT UNFSS Independent Dialogue: The Critical Role of Agricultural Extension in Advancing the 2030 Agenda: Lessons from the Field and Empirical Evidence Co-Organized by IFPRI and Sasakawa Africa Association (SAA)